2022
DOI: 10.3390/ijms23084171
|View full text |Cite
|
Sign up to set email alerts
|

2-Methoxyestradiol Inhibits Radiation-Induced Skin Injuries

Abstract: Radiation-induced skin injury (RISI) is a main side effect of radiotherapy for cancer patients, with vascular damage being a common pathogenesis of acute and chronic RISI. Despite the severity of RISI, there are few treatments for it that are in clinical use. 2-Methoxyestradiol (2-ME) has been reported to regulate the radiation-induced vascular endothelial-to-mesenchymal transition. Thus, we investigated 2-ME as a potent anti-cancer and hypoxia-inducible factor 1 alpha (HIF-1α) inhibitor drug that prevents RIS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…In addition, 2ME2 may also show therapeutic effect in dermatology. Kim's study showed that 2ME2 may be a potent therapeutic agent for radiation‐induced skin injury by reducing radiation‐induced inflammation, skin thickness, and vascular fibrosis 25 . Tang also concluded that 2ME2 showed satisfying treatment effect for psoriasis in vivo and in vitro 26 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, 2ME2 may also show therapeutic effect in dermatology. Kim's study showed that 2ME2 may be a potent therapeutic agent for radiation‐induced skin injury by reducing radiation‐induced inflammation, skin thickness, and vascular fibrosis 25 . Tang also concluded that 2ME2 showed satisfying treatment effect for psoriasis in vivo and in vitro 26 .…”
Section: Discussionmentioning
confidence: 99%
“…In this case, 2ME2 showed satisfying treating effect toward keloid fibroblasts with low drug concentration, which may also fibrosis. 25 Tang also concluded that 2ME2 showed satisfying treatment effect for psoriasis in vivo and in vitro. 26 Clinical trials have also focused on 2ME2, such as prostate cancer, 27 breast cancer, 28 and multiple myeloma.…”
Section: Ta B L Ementioning
confidence: 91%
“…In comparison to treatment after recovery from irradiation, prophylactic treatment with transdermal DFO has been found to be more effective in decreasing levels of markers of ROS and apoptosis, improving tissue perfusion, and mitigating radiation-induced skin fibrosis [ 358 ]. Another HIF-1α inhibitor, 2-Methoxyestradiol (2-ME), which is a metabolite of estradiol, has been approved as an anti-cancer drug that inhibits tubulin polymerization [ 359 ]. In a study conducted on irradiated mice, it was found that 2-ME had positive effects on radiation-induced pulmonary injury and fibrosis.…”
Section: Advances In the Treatment Of Radiation-induced Fibrosismentioning
confidence: 99%
“…Our previous study reported that 2-ME activity can induce cell death, it acts as an antiangiogenic compound and as a senescence inductor [17]. In addition, other studies showed that 2-ME also reversed metabolic-related pro-carcinogenic phenotype in osteosarcoma cells [18], inhibited skin injuries induced by radiation exposure [19], increased the infiltration of cytotoxic CD8+ T lymphocytes and the expression of PD-L1 in B16 tumors, in which authors suggest enhancing the efficacy of PD-1 blockade immunotherapy [20]. However, despite promising results, 2-ME has shown limited application due to its poor oral bioavailability (<2%) and extensive bioconjugation in vivo [21,22].…”
Section: Introductionmentioning
confidence: 96%